Mendesain Brain-Compatible Classroom: Implementasi P5 Kurikulum Merdeka Berbasis Konstruktivisme Sosial Vygotsky dalam Pendidikan Anak Usia Dini - Wulan Tini (Jurnal El-Audi, 2025)
This study aims to analyze the Brain-Compatible Classroom design in the implementation of the Pancasila Student Profile Strengthening Project (P5) based on Vygotsky's Social Constructivism theory in early childhood education institutions. The Merdeka Curriculum demands child-centered learning, but in practice, the implementation of P5 is often trapped in rigid end results (teacher-centered). The research method used is descriptive qualitative with a case study approach in inclusive kindergarten group B (ages 5-6 years). Data collection was carried out through participatory observation, in-depth interviews, and documentation of modules and project portfolios. The results show that a brain-friendly classroom is built through the creation of a low-stress environment (absence of threat) using stimulation of various textures of natural materials (loose parts). Vygotsky's principles are manifested through the utilization of the Zone of Proximal Development (ZPD) when children collaborate heterogeneously to complete environmental model projects, supported by the provision of verbal-visual scaffolding by the teacher. This integration of neuroscience and social psychology has proven effective in boosting children's collaborative, creative, and critical thinking skills naturally without cognitive coercion. This research recommends the importance of restructuring early childhood education classrooms from static to adaptive learning environments for children's brain function.